Evaluation on the application of life cycle matrix (LCM) in forecasting housing needs and housing demand in developed and developing countries - Ho, Chin Siong; Lim, Seng Boon (Faculty of Built Environment, UTM, 2008)
The accuracy of forecasting of housing needs and demand is crucial to the preparation of development plan because residential land constitutes a greater share of the developed area of cities. Presently, many common methods are based on aggregate method, headship rates, household size, backlog and other accounting methods. Many of these methods have their strengths and weaknesses contributed by the assumptions and ‘intelligent guesses’ used in the calculations. This paper aims to explore alternative method of forecasting housing needs and demand by using Life Cycle Matrix. As a household undergoes change of stages in family life cycle, one’s housing needs and demand are experiencing gradual change. Therefore, it is essential to consider the life cycle change of a household in the analysis and forecasting of housing needs and demands. Life Cycle Matrix was initiated in Japan in 1980s to estimate housing needs based on population cohort and household distribution pattern. Comparative analysis using LCM is also being carried out in developed countries (Japan and United Kingdom) and developing countries (Philippines and Malaysia).